Etika, Estetika, dan Logika dalam Berbahasa - Mac Aditiawarman (Fakultas Bahasa dan Seni UNP, 2012)
Ethic, aesthetic, and logic should take place in any language. If one of them does not exist in a sentence, it can lose its meaning. Every language in the world must contain the three of them in accordance with the development of the speakers. Using the existing ethical sense in a language of the user group, a speech may be followed by the norms of behavior, customs, and manners, and it should be prevalent in the language of the society. Aesthetics is inherent in the development of a language; it is supported by reason, thought, feeling, mind, and the beauty contained in the language which is set forth in the elections of words expressions. Furthermore, there must be logic in speaking because it is a part of the language. If the language does not contain the logic, the language of the act may be created and may not be used as a means of communication. Indeed, language is an event in which people use their thoughts, feelings, and logic, and it is more than just a means for communication. Keywords: ethic, aesthetic, logic, communication, language